Low-complexity and QoS-awared scheduling algorithm for LTE - Fei-long ZHAO (Tongxin xuebao)
Based on the relaxation based linearization principle and the greedy algorithm,a scheduling algorithm named QPF was designed with low complexity and full QoS-awared.It is divided into two parts:time and frequency domain,which can allocate all resources at once according to two service types:GBR and Non-GBR service.By this way the computation complexity decreases from O(MN)to O(M lb N).The proposed algorithm has a balanced performance in si-mulation,which can get 10% improvement in some dimensions compared with the references with high load and provide a nice trade-off between the performance and complexity.